Shenlian Extract Against Myocardial Injury Induced by Ischemia Through the Regulation of NF-κB/IκB Signaling Axis - Guo, Yuan; Yang, Qing; Weng, Xiao-Gang; Wang, Ya-Jie; Hu, Xue-Qi; Zheng, Xiao-Jun; Li, Yu-Jie; Zhu, Xiao-Xin (Frontiers in Pharmacology, 2020)
Ischemic heart disease (IHD), caused predominantly by atherosclerosis, is a leading cause of global mortality. Our previous studies showed that Shenlian extract (SL) could prevent the formation of atherosclerosis and enhance the stability of atherosclerotic plaques. To further investigate the protective effects of SL on myocardial ischemic injury and its possible mechanisms, anesthetized dogs, ex vivo rat hearts, and H9c2 cardiomyocytes were used as models. The results showed that SL had a significant protective effect on the anesthetized dog ligating coronary artery model, reduced the degree of myocardial ischemia (Σ-ST), and reduced the scope of myocardial ischemia (N-ST). Meanwhile, SL alleviated ischemic reperfusion damage in ex vivo rat hearts with improved LVEDP and ± dp/dtmax values of the left ventricle. SL reduced the pathological changes of LDH, IL-1β, MDA, and NO contents, all of which are related to the expression of NF-κB. Further analysis by Bio-Plex array and signal pathway blocker revealed that the phosphorylation of IκB was a key factor for SL to inhibit myocardial ischemic injury, and the regulation of SL on IκB was primarily related to degradation of the IκB protein. These results provided dependable evidence that SL could protect against myocardial ischemic injury through the NF-κB signalling pathway.